Impact of Thrombocytopenia in Patients With Atrial Fibrillation Undergoing Left Atrial Appendage Occlusion: A Propensity-Matched Comparison of 190 Consecutive Watchman Implantations - Zhang, Xiaochun; Jin, Qinchun; Hu, Jialu; Kong, Dehong; Pan, Cuizhen; Chen, Dandan; Chen, Shasha; Li, MIngfei; Zhou, Daxin; Ge, Junbo (Frontiers in Cardiovascular Medicine, 2021)
Objectives: The purpose of this study was to provide data on the long-term efficacy and safety of left atrial appendage occlusion(LAAO) in patients with atrial fibrillation(AF) and chronic thrombocytopenia(cTCP). Methods: Between January 2016 and December 2018, a total of 32 AF patients with thrombocytopenia (platelet count＜100*10^9/L) undergoing LAAO at our center were identified and their outcomes were compared with a propensity-matched cohort (match ratio 1:5) of patients without cTCP who had also been indicated for LAAO. Results: Between the cTCP patients and the control group, no difference was found on the incidence of stroke (0% vs 3.13%, p=0.592), systematic thromboembolisation(0% vs 0.63%, p＞0.9) and device-related thrombus (DRT) (3.13% vs 2.50%, p＞0.9). Major (12.50% vs 3.75%, p=0.065) and minor bleeding (15.63% vs 1.25%, p=0.002) was more frequent in cTCP patients but no statistical difference was reached in major bleeding. Moreover, thrombocytopenia was also identified as an independent predictor of any bleeding events (OR: 8.150, 95%CI: 2.579~25.757, p＜0.001), while an inverse relationship between higher absolute platelet count and stroke events was revealed (OR:1.015;95%CI: 1.002~1.029, p=0.022). However, in both groups we saw a significant reduction in observed annualized rates of non-procedural complications compared with the predicted values. In the cTCP and control groups, clinical thromboembolism was reduced by 100% and 74.32%, and major bleeding by 42.47% and 71.67% respectively. Conclusion: Our preliminary results indicate that LAAO using the Watchman device could be a safe and effective means of preventing stroke in AF patients with or without thrombocytopenia, but bleeding complications should be monitored intensively in cTCP patients.